Tumor budding is an independent predictor of outcome in AJCC/UICC stage II colorectal cancer - Betge, Johannes; Kornprat, Peter; Pollheimer, Marion J.; Lindtner, Richard A.; Schlemmer, Andrea; Rehak, Peter; Vieth, Michael; Langner, Cord (Annals of Surgical Oncology, 2012)
Background. In colorectal cancer, the morphology of the invasive tumor margin may reflect aggressiveness of tumor growth, thus providing important prognostic information. The tumor growth pattern according to Jass and the extent of tumor budding were analyzed in patients with American Joint Committee on Cancer/Union for International Cancer Control (AJCC/UICC) stage II disease. Methods. Tumors of 120 randomly selected patients with AJCC/UICC stage II disease were retrospectively reviewed for tumor growth pattern (expanding vs. infiltrating) and the extent of tumor budding, with high-grade budding reflecting presence of 10 or more budding foci scattered at the invasive tumor margin. Progression-free and cancer-specific survivals were determined by the Kaplan - Meier method. For multivariable analysis, Cox's proportional hazards regression models were performed. Results. The infiltrating growth pattern was significantly associated with histological subtype and lymphovascular invasion, while high-grade budding was significantly associated with tumor grade and lymphovascular invasion. High-grade budding, but not the infiltrating growth pattern, was significantly associated with outcome in univariable analysis. Cox's proportional hazards regression models proved tumor budding to be an independent predictor of disease progression (hazard ratio 3.91, 95 % confidence interval 1.3 - 11.77; P = 0.02) and cancer-related death (hazard ratio 5.90, 95 % confidence interval 1.62 - 21.51; P = 0.007). The combination of infiltrating growth pattern and high-grade budding did not have a stronger prognostic significance than tumor budding alone. Conclusions. Tumor budding independently predicted patient outcome in patients with AJCC/UICC stage II colorectal cancer and may therefore be used for accurate prognostication, patient counseling, and design of clinical trials by using integrated multimodal therapy. © Society of Surgical Oncology 2012.
CRIS-Team Scopus Importer:2025-03-05